If the numbers \[\left( {2n - 1} \right)\], \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P., then find the value of n and the numbers.
Answer
Verified
438.6k+ views
Hint: This problem is from arithmetic progression. We are given three terms in the form of n and they are in A.P. so it is clear that there is a common difference d in two consecutive terms. So we will form two equations in n and d form. One equation from first and second term and the other is from first and third term. On solving them we will get the value of n and d. from that we will find the numbers. So let’s solve it!
Step by step solution:
Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.
So let d be the common difference. Then we can write,
\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1
Now on solving the equation above we get,
\[ \Rightarrow 3n + 2 - 2n + 1 = d\]
Taking similar terms on one side we get,
\[ \Rightarrow 3n - 2n + 2 + 1 = d\]
\[ \Rightarrow n + 3 = d\] …….equation1.1
Now the difference in first and third term is 2d. then we can write,
\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2
Now on solving the equation above we get,
\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]
Taking similar terms on one side we get,
\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]
\[ \Rightarrow 4n = 2d\]
So on further simplification,
\[ \Rightarrow n = \dfrac{d}{2}\]
\[d = 2n\]
This is the value of d.
From 1.1 we get \[ \Rightarrow d - n = 3\]
Putting the value of d in the equation above,
\[ \Rightarrow 2n - n = 3\]
\[ \Rightarrow n = 3\]
This is the value of n \[ \Rightarrow n = 3\] .
Now putting the value one by one in the numbers given we get the numbers also.
First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]
Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]
Thus the numbers are \[5,11,17\].
Note:
Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.
\[
\Rightarrow n + 3 = d \\
\Rightarrow d - n = 3 \\
\Rightarrow d - \dfrac{d}{2} = 3 \\
\Rightarrow \dfrac{d}{2} = 3 \\
\Rightarrow d = 3 \times 2 = 6 \\
\]
Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Then second number \[5 + d = 5 + 6 = 11\]
Then third number \[11 + d = 11 + 6 = 17\]
Step by step solution:
Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.
So let d be the common difference. Then we can write,
\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1
Now on solving the equation above we get,
\[ \Rightarrow 3n + 2 - 2n + 1 = d\]
Taking similar terms on one side we get,
\[ \Rightarrow 3n - 2n + 2 + 1 = d\]
\[ \Rightarrow n + 3 = d\] …….equation1.1
Now the difference in first and third term is 2d. then we can write,
\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2
Now on solving the equation above we get,
\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]
Taking similar terms on one side we get,
\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]
\[ \Rightarrow 4n = 2d\]
So on further simplification,
\[ \Rightarrow n = \dfrac{d}{2}\]
\[d = 2n\]
This is the value of d.
From 1.1 we get \[ \Rightarrow d - n = 3\]
Putting the value of d in the equation above,
\[ \Rightarrow 2n - n = 3\]
\[ \Rightarrow n = 3\]
This is the value of n \[ \Rightarrow n = 3\] .
Now putting the value one by one in the numbers given we get the numbers also.
First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]
Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]
Thus the numbers are \[5,11,17\].
Note:
Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.
\[
\Rightarrow n + 3 = d \\
\Rightarrow d - n = 3 \\
\Rightarrow d - \dfrac{d}{2} = 3 \\
\Rightarrow \dfrac{d}{2} = 3 \\
\Rightarrow d = 3 \times 2 = 6 \\
\]
Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Then second number \[5 + d = 5 + 6 = 11\]
Then third number \[11 + d = 11 + 6 = 17\]
Recently Updated Pages
The correct geometry and hybridization for XeF4 are class 11 chemistry CBSE
Water softening by Clarks process uses ACalcium bicarbonate class 11 chemistry CBSE
With reference to graphite and diamond which of the class 11 chemistry CBSE
A certain household has consumed 250 units of energy class 11 physics CBSE
The lightest metal known is A beryllium B lithium C class 11 chemistry CBSE
What is the formula mass of the iodine molecule class 11 chemistry CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
What problem did Carter face when he reached the mummy class 11 english CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
In China rose the flowers are A Zygomorphic epigynous class 11 biology CBSE
What is Environment class 11 chemistry CBSE
Nucleolus is present in which part of the cell class 11 biology CBSE